Półtrepanacyjna Porównawcza Metoda Pomiaru Naprężeń - Orłoś, Z.; Dyląg, Z. (Engineering Transactions, 1959)
A discussion of the principle of the half-trepanation comparativemethod of stress measurement in structural elements. The stresses are determined on the basis of measurements of the deformation of the surface at the loaded element by making suitable drillings. This method was developed first for the purpose of examining the state of stress in an existing structural element with a real load. The theory constituting the basis of the method is described, and an analysis is made of the influence of the characteristic parameters of the system of strain gauges chosen for the measurement. Basic relations for gauges made of steel, cast iron, or siporex are established by means of laboratory tests. The principal factors influencing the accuracy of the method are discussed.